Judgment, Decision Making and Risk. - Fischhoff, Baruch (Earthscan risk in society series., 2011)
Behavioral decision research offers a distinctive approach to understanding and improving decision making. It combines theory and method from multiple disciples (psychology, economics, statistics, decision theory, management science). It employs both empirical methods, to study how decisions are actually made, and analytical ones, to study how decisions should be made and how consequential imperfections are. This book brings together key publications, selected to represent the major topics and approaches used in the field. Put in one place, with integrating commentary, it shows the common elem.